Calculation the Irreducible water saturation Swi and determination Capillary pressure curve Pc from Well Log data - Dang, Song Ha (ĐHQGHN, 2017)
Calculation o f irreducible water saturation swi and determination Capillary pressure curve Pc is very important in the Oil and gas exploration and production. The com plex reservoừs always represent a quite challenge to geologist and engineers to calculate [1]. Capillary pressure curvers are usually determined in the laboratory in core analysis and only can perform when we known the iưeducible water saturation s ^ . ị . It is very difficult in the fact. This research gives a method: Calculate s ^ ị and determine o f p ^ . curve from obtain’s data set (5 • /> ) with: j = 1 (which is easyly to collect .for every reservoừs). The method o f this study can use for both the carbonate reservoirs and the Sandstone reservoirs. These reservoirs consict o f 90% oil and gas in the world The declared actual testing result from data in variety o f diefferent huge oil fields around the world which are found on website and PVEP data has affirmed the appropriateness o f this method.